Uporaba optimalnega časa ustavljanja na zavarovalniških produktih - Orelj, Maša (Matrika, 2024)
The theory of optimal stopping time helps us answer the question, at what point in time the expected benefit of stopping a random process is maximized. Although the theory is applicable in many fields, this article will focus on its application in insurance products with guarantees. The risk arising from such products must be hedged by suitable investments.At the beginning of the article we give a general introduction to the mathematical basis of the theory, define the concept of Snell envelope and present its applicability.This is followed by a practical use of the theory, where we present two hedging strategies of an insurance company. One of the theories is based on finding the most appropriate time to buy a put option, which, at the expiry of the contract,provides sufficient funds to pay out the guaranteed amount. The two strategies are compared with respect to the insurer’s ultimate loss distribution, and the results are supported by a short simulation.
Keywords: insurance; optimal stopping time; optimalni čas ustavljanja; probability; Snell envelope; Snellova ovojnica; verjetnost; zavarovalništvo